2020
DOI: 10.1111/jcmm.15827
|View full text |Cite
|
Sign up to set email alerts
|

Emodin inhibiting neutrophil elastase‐induced epithelial‐mesenchymal transition through Notch1 signalling in alveolar epithelial cells

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…Repeated damage to the alveolar epithelial cells induced by various harmful factors has been accepted as the first and foremost cause of pulmonary fibrosis and complex networks of cytokines are involved in this process, as well as the subsequent tissue repair and fibrosis [30]. Here, a well-validated model of EMT in the A549 human alveolar cell line was used to study the mechanism of pulmonary fibrosis, for which a suite of morphological, phenotypic and functional markers and outcomes have been well characterized [31][32][33]. BLM is widely used as an inducer of pulmonary fibrosis in animal models [34], and similar effects were validated in vitro experiments, and EMT characteristics were detected in BLM treated A549 cells [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Repeated damage to the alveolar epithelial cells induced by various harmful factors has been accepted as the first and foremost cause of pulmonary fibrosis and complex networks of cytokines are involved in this process, as well as the subsequent tissue repair and fibrosis [30]. Here, a well-validated model of EMT in the A549 human alveolar cell line was used to study the mechanism of pulmonary fibrosis, for which a suite of morphological, phenotypic and functional markers and outcomes have been well characterized [31][32][33]. BLM is widely used as an inducer of pulmonary fibrosis in animal models [34], and similar effects were validated in vitro experiments, and EMT characteristics were detected in BLM treated A549 cells [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…The transition of AECs into mesenchymal cells has been reported to cause and/or aggravate PF [ 6 ]. In this study, the direct effects of PTUPB on the TGF- β 1-induced EMT were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…EMT is involved in wound healing, fibrosis, embryonic development, and cancer metastasis [ 5 ]. Most investigators concur that alveolar type II epithelial cells undergo EMT during PF development [ 6 , 7 ]. Studies have shown that pulmonary fibroblasts are derived from various routes, of which about one-third are derived from alveolar type II epithelial cells via EMT [ 8 ].…”
Section: Introductionmentioning
confidence: 98%
“…Emodin at 10 μg/ml significantly inhibited the enzymatic activity of neutrophil elastase, which then inhibited nuclear notch-mediated EMT, and subsequently inhibited ECM production. These studies not only highlighted the critical roles of neutrophil infiltration and Notch1 signaling in IPF progression but also emphasized the plausible therapeutic effects of emodin for the treatment of IPF [ 81 ]. Furthermore, researchers also found that anti-fibrosis benefits of emodin (0.3 or 1 mg/kg) were related to down-regulation of SMAD ubiquitination regulatory factor 2 and up-regulation of Smad7 in surgery-induced renal fibrotic rats [ 82 ].…”
Section: Pharmacological Effects Of Emodinmentioning
confidence: 99%